The effect of reciprocal learning and self-efficacy on students learning outcomes at the University of Muhammadiyah Jember - A'yun, Qurrota; Handayani, Luluk; Sujiwo, Dimas Anditha Cahyo; Maula, Inayatul; Rahma, Restu Aulia (International Journal of Trends in Mathematics Education Research, 2023)
Every learning activity must involve students so that they can experience what they are learning. In order to achieve the best learning results, students must be actively involved in learning activities. Reciprocal learning is an independent learning activity in learning subject matter as well as an active and creative role as an educator in conveying all information to his friends. The existence of student confidence in active and independent learning will have a positive effect on student learning outcomes. Instruments used in the form of questionnaires and tests. The questionnaire is in the form of a number of written questions used to obtain information from the respondent, while the test is in the form of a list of questions or items. The analysis in this study uses multiple linear regression tests. The results of the study show that: (1) there is a significant influence between the use of reciprocal learning and the learning outcomes of IT students at the Muhammadiyah University of Jember; (2) there is a significant influence between self-efficacy and the learning outcomes of IT students at the Muhammadiyah University of Jember; and (3) there is an effect of the use of reciprocal learning and self-efficacy simultaneously or together on the learning outcomes of IT students at the Muhammadiyah University of Jember.